Chemical forces study of heat-induced myofibrillar protein gel as affected by partial substitution of NaCl with KCl, MgCl2 and CaCl2. Issue 2 (2nd April 2016) - Zhang, Ziye; Yang, Yuling; Tang, Xiaozhi; Chen, Yinji; You, Yuan
Abstract : The effects of the partial substitution of NaCl with KCl, MgCl2 and CaCl2 on the chemical forces and hardness of heat-induced myofibrillar protein (MP) gel were investigated. Compared with the normal-sodium-level MP gels (0.6 mol/L NaCl), low-sodium-level MP gels (0.4 mol/L NaCl) resulted in weaker disulphide bonds, hydrophobic interactions, electrostatic interactions, and stronger hydrogen bonds. Partial substitution of NaCl with KCl had no significant impacts on the chemical forces. MgCl2 and CaCl2 contributed to stronger hydrophobic interactions, and weaker hydrogen bonds and electrostatic interactions ( p < 0.05), while they had no significant impacts on disulphide bonds. Gel hardness was weakened with the low level of sodium, and strengthened with the substitution of NaCl with MgCl2 and CaCl2 . The enhancement of gel hardness with the substitution of NaCl with MgCl2 and CaCl2 suggested that stronger attractive forces and weaker repulsive forces contributed to stronger hardness.